The use of teledentistry in clinical oral and maxillofacial pathology practice: an institutional experience - Flores-Hidalgo, Andres; Collie, John; King, Shae; Grant, Ford T.; Beasley, Nicole E.; Moss, Mark E.; Tempel, Thomas R. (Frontiers in Oral Health, 2023)
Background. Although there has been a slight increase in dental professionals since 2011, 98 of North Carolina's 100 counties are designated as Dental Health Professional Shortage Areas by the Heath Resources and Service Administration. This shortage significantly increases disparities and access to primary and specialized oral health care. Also, dental professionals in these remote locations may feel the access and referrals to oral and maxillofacial pathologists cumbersome. In 2020, the COVID-19 pandemic prompted an inevitable surge in the use of digital technology due to the social distancing norms and lockdowns, which forced dental education institutions and practitioners to adjust to new ways of meeting, teaching, and providing dental care. In the present manuscript, we report our institutional experience delivering specialized dental care in rural areas.We conducted a retrospective case series of diagnosis, management, and outcomes of patients who underwent synchronous or asynchronous virtual and remote examination of oral lesions at ECU School of Dental Medicine and one satellite clinic over seven years. For those cases that concluded on surgical sampling, the clinical impressions, differential diagnoses, and the final diagnosis were compared to assess the accuracy of the clinical exam through teledentistry.Results. The total study population consisted of 71 patients. Most of the remote consultations were done asynchronously. Also, most virtual clinical consultations were initiated due to clinical suspicion of malignancy and infectious/reactive conditions, accounting for 42% and 25.3% of all encounters.Conclusions. The presented data suggest how teledentistry can support clinical practice in rural areas to achieve optimal care for the patient in rural or remote communities. Also, it significantly decreases the travel required, the number of appointments, and increases the speed of diagnosis. Teledentistry is an excellent tool available to all clinicians and can dramatically aid in diagnosing oral mucosa lesions.